Effect of a training program on the development of physical abilities in football goalkeepers - Al-Nedawy , Rand Issa Abboud; Saeed Al-Mousawi , Suhad Qassem (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The primary aim of this study was to find out the effect of a training program on the development of physical abilities in football goalkeepers. The current study was conducted on goalkeepers of the Academy of Espanyol Sports Club in the premises of Haifa Sports Club Stadium. The study was completed by the researchers within the timeline of May 2021 to August 2021. A total of 7 goalkeepers falling within the age group of 15-17 years were recruited as the sample participants for the study. Out of 7 goalkeepers, 5 goalkeepers were included in the primary experiment and 2 of them were excluded. The training program applied had a positive effect on the development of physical abilities in the football goalkeepers of the sample. Therefore, the authors recommend to use the training program presented in this study to improve physical abilities in football goalkeepers.